2009
DOI: 10.1111/j.1365-2095.2008.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of practical diets containing different protein levels on gonad development of female redclaw crayfishCherax quadricarinatus

Abstract: The effect of five experimental diets with different crude protein content (220, 270, 330, 390 and 450 g kg )1 ) on gonad development of female Cherax quadricarinatus was tested under laboratory conditions. After 70 days, a significant linear relationship indicated that higher concentrations of protein and carbohydrates in the hepatopancreas were produced as the dietary crude protein increased (P < 0.05). There were significant responses of the gonadosomatic index, hepatosomatic index, biochemical composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
5
18
0
Order By: Relevance
“…Similar to previous reports (Rodríguez‐González et al . ), in this study, females fed diets containing the higher protein content (32%) accumulated more protein in the gonad. An increase in protein content in the gonad of female redclaw crayfish is attributed to active mobilization of energy reserves from exogenous sources to the gonad and their introduction to the oocyte by endocytosis (Abdu et al .…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Similar to previous reports (Rodríguez‐González et al . ), in this study, females fed diets containing the higher protein content (32%) accumulated more protein in the gonad. An increase in protein content in the gonad of female redclaw crayfish is attributed to active mobilization of energy reserves from exogenous sources to the gonad and their introduction to the oocyte by endocytosis (Abdu et al .…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies have shown that diets with 26–33% P and 8% L optimized growth and survival during juvenile (Cortés‐Jacinto, Villarreal‐Colmenares, Cruz‐Suárez, Civera‐Cerecedo, Nolasco‐Soria & Hernandez‐Llamas ) and pre‐adult stages of the redclaw crayfish (Cortés‐Jacinto, Villarreal, Civera‐Cerecedo & Naranjo‐Páramo ). A dietary protein level of 32% has been recommended for gonad development (Rodríguez‐González, Villarreal‐Colmenares, García‐Ulloa & Hernández‐Llamas ) and reproduction of female redclaw crayfish Rodríguez‐González, García‐Ulloa, Hernández‐Llamas, & Villarreal, ). The objective of this study was to define the effect of different dietary protein and lipid concentrations on gonad maturation of the female C. quadricarinatus .…”
Section: Introductionmentioning
confidence: 99%
“…Maternal provision of nutrients is important for the development of the embryo and plays a significant role in offspring performance (Carboni, Hughes, Atack, Tocher, & Migaud, ; Izquierdo, Fernandezpalacios, & Agj, ). During ovarian development, dietary and maternal reserves are mobilized and transported into the oocytes (Rodríguez‐González, Villarreal, García‐Ulloa, & Hernández‐Llamas, ), where they provide energy and nutritional requirements for the growth and development of the embryos and yolk‐sac larvae until the start of exogenous feeding (Rodríguez‐González et al., ). Although the basic nutritional requirement such as protein (Arzel, Metailler, Huelvan, Faure, & Guillaume, ; Arzel, Metailler, Kerleguer, Le Delliou, & Guillaume, ; Arzel, Metailler, Le Gall, & Guillaume, ) and lipid (Arzel et al., ; Regost, Arzel, Cardinal, Laroche, & Kaushik, ; Turchini et al., ) of brown trout during the grow‐out period has been previously established, the dietary requirements of broodstock reared in freshwater for optimal production and reproductive performance are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Rodríguez‐González, Villarreal, García‐Ulloa and Hernández‐Llamas () obtained better gonad development in 33% crude protein with a protein: energy ratio of 15.6 mg kJ −1 diet for female C. quadricarinatus . In addition, Carmona‐Osalde, Olvera‐Novoa and Rodríguez‐Serna () reported similar results for another crayfish species, Procambarus llamasi .…”
Section: External Factorsmentioning
confidence: 93%